Beauty and the beast (Cottage Farm, England autumn publishing, 2021)
Belle dreams of a more exciting life, while the cursed Beast stays cooped up in his castle. Will they be able to break the spell before it's too late ? Find out in this wonderful story to enjoy at bedtime
English stories
Keywords: English stories